Evaluasi Implementasi Kebijakan Pendidikan dalam Perspektif Filsafat Pendidikan di Indonesia - Sirajuddin; Ahmad, Masduki; Suryadi (Ikatan Da'i Indonesia, 2025)
This study aims to describe the evaluation of the implementation of Education policy in the perspective of the philosophy of Education in Indonesia. This study uses a literature study method by observing various documents from books and journals. The literature study in this study focuses on researching literature related to Education policy in Indonesia, the philosophy of Education, and the evaluation of education policy. Data collection was carried out by collecting library data, reading, recording, and managing research results objectively, systematically, analytically, and critically by looking at the year of publication and the most recent research. The results of this study indicate that the implementation of Indonesian Education policy has the potential to improve the quality of education, but also faces various challenges. Disparities in education and teacher quality are key factors that need to be considered in policy evaluation. Therefore, it is important to conduct continuous evaluation of education policy to ensure that education goals can be achieved effectively. The government needs to evaluate policy implementation so that education goals can be achieved.